A randomized, double-blind, dose ranging clinical trial of intravenous FDY-5301 in acute STEMI patients undergoing primary PCI - Adlam, D; Zarebinski, M; Uren, NG; Ptaszynski, P; Oldroyd, KG; Munir, S; Zaman, A; Contractor, H; Kiss, RG; Édes, I; Szachniewicz, J; Nagy, GG; et al. (Elsevier, 2021)

(untitled)
Background Ischemia-reperfusion injury remains a major clinical problem in patients with ST-elevation myocardial infarction (STEMI), leading to myocardial damage despite early reperfusion by primary percutaneous coronary intervention (PPCI). There are no effective therapies to limit ischemia-reperfusion injury, which is caused by multiple pathways activated by rapid tissue reoxygenation and the generation of reactive oxygen species (ROS).